IMPLEMENTASI METODE PENGAJARAN QI-RA`AT SAB`AH DI PONDOK PESANTREN AL-QUR'AN ASY SYIFA - Zaini Hafidh; Wahyu Andi Saputra; Ary Mutawalie (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
This research departs from the implementation of the qira'at sab'ah teaching method where the defense of qira'at sab'ah uses the sorogan method and the talaqqi (face to face) method. The purpose of this study is to determine the implementation and impact of the Qira'at Sab'ah teaching method in the Asy-Syifa Islamic boarding school. This research uses a descriptive method with a qualitative approach. Data collection techniques are carried out by means of observation, interviews, and analyzing documents. The results of this study show that the implementation of qira'at sab'ah learning in the asy-syifa Islamic boarding school has 2 stages, namely the first stage of pre-recitation, in this stage students are required to do sorogan to the old students who are appointed to be able to guide intensely at dawn and maghrib. The second stage is the stage of recitation. In this stage, students who are in accordance with the qualifications are fluent in reading the history of Hafs and have mastered the rules of tajwid will talaqqi directly to the leadership, namely KH. Ujang Hidayat.